Enablers and barriers to rotavirus vaccine coverage in Assam, India- A qualitative study - Rashmi Mehra; Arindam Ray; Sabita Das; Biman Kusum Chowdhury; Seema Singh Koshal; Rhythm Hora; Amrita Kumari; Amanjot Kaur; Syed F. Quadri; Arup Deb Roy (Vaccine: X, 2024)
Background: Estimates suggest that 78,000 children died due to rotavirus gastroenteritis annually between 2011 and 2013 in India. The north eastern state of Assam reported 38.4% pediatric diarrheal admissions testing positive for rotavirus. Rotavirus vaccine (RVV) was introduced in Assam in 2017 following which the National Family Health Survey-5 (NFHS-5) (2019) revealed low RVV coverage in Assam with wide variation between the districts. the current study was conceptualized and undertaken to capture the enablers and barriers to RVV coverage in Assam. Methods: Qualitative study conducted in 5 randomly selected districts in Assam. Participants (key informants) were recruited by purposive sampling at each level of the health system including healthcare officials, service providers and caregivers based on availability. Thirty-five in-depth interviews (IDIs) and five focus group discussions (FGDs) were conducted. Interviews were tape recorded and transcribed. Data was coded and analyzed using the thematic framework approach. Results: Findings from the qualitative data collection were collated and analyzed under 7 identified themes. Difficult terrain, limited service provider availability and no catch-up training for new recruits were some of the barriers to RVV coverage. In contrast, Information, Education & Communication (IEC) in vernacular language, RVV safety profile, development partner support and adequate RVV supply were identified as some of the enablers of RVV coverage. Conclusion: Few broad recommendations to overcome identified barriers include comprehensive inter-sectoral coordination, regular monitoring and frequent refresher training sessions. There is a need for a future study utilizing existing coverage data and larger sample size to triangulate the findings of this study.